Positive Attitude Upper Middle School social and emotional learning program: influences of implementation quality on program outcome - Coelho, Vítor Alexandre; Marchante, Marta; Brás, Patrícia (Frontiers in Psychology, 2023)
Introduction There is an increased call for studies analyzing how implementation quality influences Social and Emotional Learning (SEL) program effectiveness. Methods The current dissemination study analyzed the effectiveness of the Positive Attitude Upper Middle School SEL program on a Portuguese nationwide sample composed of 813 middle school students (7th and 8th grade; 51.7% boys; Mage = 12.41, S.D. = 1.06), from 36 classrooms (Mclassroom = 22.58; S.D. = 2.86), distributed between the control group (179 students), and three intervention groups (643 students) that reflected low, middle, and high implementer experience (respectively, Gulbenkian Academies of Knowledge, Positive Attitude Cadaval and Positive Attitude Torres Vedras). Dosage and fidelity (as implementation quality dimensions), gender, and classroom size (as individual and classroom-level variables) were also analyzed. Self-report questionnaires were administered pre- and post-intervention and at a 6-month follow-up. Results Multilevel models were employed, and results showed that participating in the PAUMS SEL program led to more positive trajectories in self-control, social awareness, relationship skills, and responsible decision-making when compared with control groups. Regarding implementation quality, only the implementer’s experience impacted the effectiveness of the PAUMS SEL program; students in the Gulbenkian Academies of Knowledge intervention group displayed a less positive trajectory in self-control than students in the Positive Attitude Torres Vedras intervention group. Discussion Altogether, results showed that the PAUMS SEL program is ready for dissemination in Portugal, although a higher level of implementer experience is needed to achieve the best effectiveness, and they support the importance of analyzing implementer experience in SEL programs’ effectiveness studies.